Implementation of circuit of culture theory in Surabaya's integrated public transportation services towards the culture of choosing modern public transportation - Novianty, Restu Dinda (Universitas Wiralodra, 2024)
This article aims to see the implementation of the circuit of culture theory in Surabaya's integrated public transportation services towards the culture of choosing modern transportation. One of the modern-based public transportation in Surabaya is the Suroboyo Bus. This research uses a qualitative descriptive method, with the help of the circuit of culture theory coined by Stuart Hall. Based on the implementation of the circuit of culture theory in this discussion, it can be seen from three aspects, namely representation, identity, and consumption. The choice of modern public transportation is seen as a cultural phenomenon in society. People tend to choose public transportation which has the best facilities, affordable fares, and makes driving safe and comfortable. The Suroboyo bus has been programmed by the Surabaya City government since 2018. One of the missions to be achieved is to make the Suroboyo bus a modern form of transportation that is popular with the public and reduces congestion. However, the number of traffic jams cannot be reduced if social control is not carried out through a civilization process, namely disciplining people's behavior and attitudes in traffic.